Land Tenure and Its Relation on Food Security (A study of Dolakha District) - Rawal, Sunil (Patan Pragya, 2021)
This writing discusses on Land Tenure and its relation on Food Sufficiency from a sociological perspective. Land Tenure and Food Security is an interdisciplinary concept that makes it easy to see from sociological lenses. The issues of food security concern with the management of food resources to combat the people from food deficit, shortage, starvation and diseases whereas land tenure is the system that refers to arrangement orright under which the holder holds or uses holding land. The food security and land tenure is one of the political-economic discourses, where livelihood, geographic exclusion, food production, distributions and accessibility largely discussed. I would like to examine relationship between land tenure and food security at Dolakha district. Which causes effects of food insecurity challenging it and risking to food security contingently? In this essay, I would like to explore the significance of food security from primary and secondary information from the different literatures to conceptualize the term food security.